2008
DOI: 10.2202/1556-3758.1491
|View full text |Cite
|
Sign up to set email alerts
|

Fruits & Vegetables Drying Combining Hot Air, DIC Technology and Microwaves

Abstract: Dehydration of fruits and vegetables is one of the most ancient and efficient preservation methods. The quality of the product and its cost depend mainly on the final stage of drying. In the present paper we analyze physical mechanisms occurring during drying throughout heat and mass transfer for defining an efficient and economic three stage drying process of hot air drying combined to a texturing stage by DIC (Instant Controlled Pressure Drop) and finally using microwave assisted by ambient temperature air d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…DIC has been tested in different fruits (Alonzo-Mací as, Cardador-Martí nez, Mounir, Montejano-Gaitá n, & Allaf, 2013;Haddad, Mounir, Sobolik, & Allaf, 2008;Mounir, Allaf, Berka, Hassani, & Allaf, 2014) where authors report shorter drying and rehydration times, as well as lower final water content in the fruits due to the rapid removal of water as the diffusivity was improved. Alonzo-Mací as et al (2013) reported an increase of antioxidant activity in strawberries with DIC compared to hot air drying and freeze-drying.…”
Section: C) Ether Extract (% Db) D) Frap Antioxidant Capacity (μMol mentioning
confidence: 99%
“…DIC has been tested in different fruits (Alonzo-Mací as, Cardador-Martí nez, Mounir, Montejano-Gaitá n, & Allaf, 2013;Haddad, Mounir, Sobolik, & Allaf, 2008;Mounir, Allaf, Berka, Hassani, & Allaf, 2014) where authors report shorter drying and rehydration times, as well as lower final water content in the fruits due to the rapid removal of water as the diffusivity was improved. Alonzo-Mací as et al (2013) reported an increase of antioxidant activity in strawberries with DIC compared to hot air drying and freeze-drying.…”
Section: C) Ether Extract (% Db) D) Frap Antioxidant Capacity (μMol mentioning
confidence: 99%
“…The last operation allows residual water to instantly autovaporize, inducing rapid cooling and controlled expansion of the product [1]. DIC treatment allows various heat-sensitive foodstuffs to expand while obtaining a very satisfactory quality [3].…”
Section: −1mentioning
confidence: 99%
“…The applicable methods available in food drying process industry are solar, spray, freeze, vacuum, osmotic, cabinet or tray, fluidized bed, spouted bed and microwave drying (George et al 2004). DIC, which is another alternative of drying methods, has been used for swell-drying of fruits and vegetables drying (Louka and Allaf 2002;Al Haddad et al 2008), texturing and drying various biological products by instant auto vaporization Nouviaire et al 2008;Kristiawan et al 2011), and microbiological decontamination (Setyopratomo et al 2009), post harvesting and/or steaming paddy rice (Pilatowski et al 2010) and essential oil extraction (Amor et al 2008;Besombes et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The usage of DIC could greatly intensify the limiting transfer phenomenon, improve texture and usually maintain the product color, vitamins and flavor, reduce energy consumption and most importantly provide environmental friendly process (Al Haddad et al 2008;Pilatowski et al 2010). To ensure a high quality of food, the improved of both the kinetics and the capacity for dehydration and rehydration is emphasized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation